2014
DOI: 10.3109/13645706.2014.886594
|View full text |Cite
|
Sign up to set email alerts
|

Pain, well-being, body image and cosmesis: A comparison of single-port and four-port laparoscopic cholecystectomy

Abstract: SILS patients have significantly reduced one-week pain scores and there was no significant difference in well-being between the two groups. Patients who underwent SILS had improved body image and cosmesis. If both techniques are found to be equivalent concerning safety, cost, learning curve and availability, SILS may play a key role in the new era of patient choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A recent study also reports significantly lower pain one week postoperatively, even though no significant difference was found in analgesic requirement (27). However, opponents of this technique argue that the umbilical incision is obviously smaller in 4-PLC because only one trocar for the camera has to be inserted instead of all instruments.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study also reports significantly lower pain one week postoperatively, even though no significant difference was found in analgesic requirement (27). However, opponents of this technique argue that the umbilical incision is obviously smaller in 4-PLC because only one trocar for the camera has to be inserted instead of all instruments.…”
Section: Discussionmentioning
confidence: 96%
“…When performing RPC for ulcerative colitis (UC) the main argument for a purely laparoscopic approach is to diminish the fall in fecundity experienced by female patients of child‐bearing age who have had open surgery . Most patients who require surgery for UC are young and prefer a laparoscopic approach as the cosmetic results are superior to those of open surgery .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that SIRC or SILC was associated with less postoperative pain than 3PLC or four-port laparoscopic cholecystectomy (4PLC). [18][19][20] Contrary to these results, however, other studies reported that 3PLC and 4PLC each produced better postoperative pain outcomes than SIRC or SILC because of the larger umbilical fascial incision and movements within that space and the greater pressure. 21,22 The exact mechanism has not yet been established, and the pain is subjective to the individual, making it difficult to compare among patients.…”
Section: Discussionmentioning
confidence: 79%